2019
DOI: 10.3390/agriculture9050103
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Series Analysis of Climate Variability in Urban and Agricultural Sites (Rome, Italy)

Abstract: Identifying early signals of climate change and latent patterns of meteorological variability requires tools analyzing time series data and multidimensional measures. By focusing on air temperature and precipitation, the present study compares local-scale climate regimes at two sites in Central Italy (urban Rome and a peri-urban cropland 10 km west of Rome), using descriptive and inferential statistics on both variables and a drought index (the Standardized Precipitation Index, hereafter SPI) recorded over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 99 publications
1
8
0
Order By: Relevance
“…For many cities around the world, warming trends in minimum and maximum daily temperatures were calculated from stations located in urban environments. For some of them, the comparison with nonurban data shows that the trends are mainly related to large-scale climate change (129,130) without significant modification by cities. Nevertheless, Lee et al (131) studied several Asian megacities and found that the urbanization dynamics between 1992 and 2012 led to a modification of climatic trends.…”
Section: Learning From Past Trends and Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many cities around the world, warming trends in minimum and maximum daily temperatures were calculated from stations located in urban environments. For some of them, the comparison with nonurban data shows that the trends are mainly related to large-scale climate change (129,130) without significant modification by cities. Nevertheless, Lee et al (131) studied several Asian megacities and found that the urbanization dynamics between 1992 and 2012 led to a modification of climatic trends.…”
Section: Learning From Past Trends and Eventsmentioning
confidence: 99%
“…Some work also looked at long-time series of precipitation observations. Although several climatological studies show an effect of cities on the intensification of precipitation, there is no evidence of an impact of cities on the evolution of climate trends (129,130,134). Nevertheless, based on an integrative indicator combining temperature and precipitation data, Salvati et al (130) showed an increase in drought events at the city site (Rome, Italy) relative to the rural site between 1958 and 2017.…”
Section: Learning From Past Trends and Eventsmentioning
confidence: 99%
“…The climate is typically Mediterranean, with rainfall concentrated mainly in autumn and spring, and a mild temperature in winter. The average long-term annual rainfall and mean daily temperature in Rome were 700 mm and 16 • C, respectively [59]. Despite a relatively high human pressure, the original landscape typical of dry Mediterranean ecosystems was preserved in several woodlots and mixed agro-forest patches (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…On the other hand, Rome is a larger city of 3.7 million people, which is located in central-west Italy in a valley enclosed by mountains (Colli Albani, Sabatini and Tolfa mounts, not exceeding 1300 m). The climate of the city is similarly characterized by hot summers and mild winters, with mean annual temperature of~16.5 • C and mean annual precipitation of 802 mm [88]. * Cumulus parametrization is only used in d01 and d02.…”
Section: Study Areasmentioning
confidence: 99%